Indigenous Peoples Rights under International Law - Charters, Claire (The New Zealand Yearbook of International Law, 2007)
2007 was a significant year for Indigenous peoples and international law. The United Nations (UN) General Assembly adopted the Declaration on the Rights of Indigenous Peoples (the Declaration on Indigenous Peoples), after more than 20 years of negotiations, and the Human Rights Council established the Expert Mechanism on the Rights of Indigenous Peoples (the EMRIP). Further, the World Intellectual Property Office (WIPO) continued its work on traditional knowledge, as did the working groups associated with the Convention on Biodiversity (CBD). Indigenous issues were considered in institutions such as the World Health Organisation (WHO) and, of course, the Permanent Forum on Indigenous Issues. New Zealand was also the subject of review by the UN Committees on the Elimination of Racial Discrimination (CERD Committee) and the Elimination of Discrimination Against Women (CEDAW Committee) on its compliance with its human rights obligations, some of which raised issues involving Maori. This review details New Zealand's state practice in these institutions.
Keywords: Human rights; Indigenous peoples (International law); Indigenous peoples–Civil rights; Indigenous peoples–Legal status; laws; etc.; New Zealand

Māori Electoral Participation - Fitzgerald, Eljon; Stevenson, Brendan; Tapiata, Jacob (A Report Produced for the Electoral Commission by the Best Outcomes for Māori: Te Hoe Nuku Roa Group. http://www. elections. org. nz/research-statistics/research/participation-research, 2007)

It's quite simple really - Jackson, Moana (Yearbook of New Zealand Jurisprudence, 2007)

Tikanga as the first law of Aotearoa - Mikaere, Ani (Yearbook of New Zealand Jurisprudence, 2007)

Tino rangatiratanga : water under the bridge? - Bargh, Maria (He pūkenga kōrero: a journal of Māori studies, 2007)
Argues that Māori have been actively engaged in practising tino rangatiratanga in various forms even since before the Declaration of Independence ...
Keywords: colonisation; constitution; government; international relations; iwi; kaitiakitanga; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights

White Mothers, Brown Children: Ethnic Identification of Maori-European Children in New Zealand - Kukutai, Tahu H (Journal of Marriage and Family, 2007)
Studies of multiethnic families often assume the ethnic identification of children with the minority group results from the minority parent. This study examines an alternate view that mainstream parents also play an important role in transmitting minority ethnicity. It explores this argument using data from New Zealand on the ethnic labels mothers assign to their Maori-European children. It finds that European mothers are just as disposed as Maori mothers to designate their child as Maori, either exclusively or in combination. Two explanations, grounded in ethnic awareness and gendered inheritance, are proposed. Although neither satisfactorily predicts maternal designation decisions, the readiness of European mothers to identify their child as Maori underscores their role in diffusing Maori ethnicity.
Keywords: ethnic identity; ethnicity; interethnic marriage